(untitled) (Journal of Economic Research & Business Administration, 2023)
The stress resistance of banks is important for the entire financial system of the country, since the banking sector is the most important segment of the economy. Banks accumulate free resources and ensure the movement of money for the needs of the economy. Stress testing is one of the methods for assessing the stability of banks to various stressful situations in the financial market. In the economic literature, this aspect has been given enough attention, but to a greater extent with respect to certain types of risks. Studies have approached the issue of assessing the stress resistance of banks in different ways. Some considered the problem through the prism of assessing the probability of bankruptcy, others used an assessment of the dependence of banks’ profitability on various factors. Most of the authors used regression, cluster, discriminant analysis and various stress testing methods. In this study, both classical methods are used - collection, synthesis, analysis, generalization, processing and visualization of data - and methods of stress testing and scenario modeling. Data collection was carried out on the basis of data from the Bloomberg information database for banks in Turkey and Kazakhstan. Unfortunately, not all commercial banks in Turkey and Kazakhstan managed to collect data for 2020-2022. At the same time, this article uses a scenario stress testing method based on the Bloomberg method. The analysis made it possible to determine that Turkish banks are more sensitive to crises, especially for such banks as Turkiye Sinai Kalkinma Bankasi and Sekerbank Turk AS, for which the values are always significantly higher than the median. Banks of Kazakhstan are more resistant to crises and less responsive to market changes, except for Kaspi.KZ JSC, whose performance is close to that of Turkish banks. Key words: Stress testing, banking, stress resistance, Bloomberg method, forecasting